2014
DOI: 10.4196/kjpp.2014.18.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cellular Calcium Metabolism in Radiation-sensitive RKO Human Colorectal Cancer Cells

Abstract: Radiation therapy for variety of human solid tumors utilizes mechanism of cell death after DNA damage caused by radiation. In response to DNA damage, cytochrome c was released from mitochondria by activation of pro-apoptotic Bcl-2 family proteins, and then elicits massive Ca2+ release from the ER that lead to cell death. It was also suggested that irradiation may cause the deregulation of Ca2+ homeostasis and trigger programmed cell death and regulate death specific enzymes. Thus, in this study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Recent studies have shown that Ca 2+ also contributes to some malignant behaviors in tumors, such as proliferation, invasion, migration, and metastasis [13]. The imbalance of intracellular Ca 2+ influx is closely related to the hallmarks of various cancers including colorectal cancer [14, 15]. Given that TRPV1 is a powerful nonselective Ca 2+ channel, we hypothesize that TRPV1 can affect the growth of colorectal cancer cells by regulating Ca 2+ dependent signaling.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have shown that Ca 2+ also contributes to some malignant behaviors in tumors, such as proliferation, invasion, migration, and metastasis [13]. The imbalance of intracellular Ca 2+ influx is closely related to the hallmarks of various cancers including colorectal cancer [14, 15]. Given that TRPV1 is a powerful nonselective Ca 2+ channel, we hypothesize that TRPV1 can affect the growth of colorectal cancer cells by regulating Ca 2+ dependent signaling.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, chrysin exhibited anti-tumor activity against choriocarcinoma cells through modification of mitochondrial membrane potential, disruption of Ca 2+ levels in cytosol, enhancing generation of reactive oxygen species (ROS), and inducing lipid peroxidation, which affects intracellular Ca 2+ homeostasis resulting in cancer cell damage [ 86 ]. Radiation therapy employs a cell death mechanism triggered by DNA damage, which activates pro-apoptotic Bcl-2 family proteins and evokes enormous Ca 2+ release from the endoplasmic reticulum, resulting in cell death [ 87 ]. Moreover, low doses of ionizing radiation (0.1–0.5 Gy) were found to suppress intracellular (Ca 2+ ) influx in the activated rat basophilic leukemia [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…While, chrysin showed antiproliferative activity by suppressing p38 MAPK expression, which involved JNK and NF-κB in cardiac cells [ 102 ]. Exposure to low dose of ionizing radiation was found to suppress cancer cell proliferation via suppressing p38 kinase in MCF-7 human breast cancer cells [ 103 ], inhibiting JNK as well as ERK phosphorylation [ 87 ], and down-regulating NF-κB through suppressing TNFα-induced degradation of inhibitor of kappa B (IκB) protein and release of p65 subunit to the nucleus, reducing NF-κB activity [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the size of these teeth is significantly larger than in Prodremotherium from the old Quercy collections [ 64 ] and Pech Desse [ 17 ]. The teeth are more selenomorph than in “ Amphitragulus ” and Bedenomeryx [ 8 ], [ 68 ], [ 77 ] and the parastyle is not that anteriorly projected than observed on “ Amphitragulus ” feningrei [ 62 ], [ 78 ], [ 79 ]. Looking at the neodiagnosis proposed by Mennecart [ 8 ], these fossils include all indicating features of Dremotherium .…”
Section: Systematic Paleontologymentioning
confidence: 99%